Toward quantum-resistant strong designated verifier signature. (1st January 2014) - Sun, Xi; Tian, Haibo; Wang, Yumin
This paper proposes two Strong Designated Verifier Signature (SDVS) schemes based on two post-quantum key agreement protocols. One protocol is based on a problem about an isogeny between supersingular elliptic curves. The problem is hypothetically strong against a quantum computer. Another protocol is based on the computational difficulty to solve multivariate algebraic equations of high degree. Our proposals are the first instantiations of a basic design idea about SDVS that are potentially secure against a quantum computer.